2012
DOI: 10.1002/pbc.24326
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent perspectives on phase I cancer research

Abstract: Background The aim of this study was to examine adolescent patients’ perspectives on their understanding and decision making about a pediatric Phase I cancer study. Procedure Participants included adolescents ages 14-21 years with cancer (N = 20), all of whom attended a Phase I study consent conference. Participants responded to closed- and open-ended questions on a verbally administered structured interview, which assessed aspects of understanding and decision making about the Phase I study. Results All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 28 publications
4
72
0
Order By: Relevance
“…In addition, physicians and parents may fail to engage children and adolescents in the discussion or actively interfere with their involvement (e.g., interrupting or answering a question that was directed to the child) 24 . The physician’s expectation that the parent will make the final decision is likely to limit attempts to engage the patient in trial or treatment discussions 25, 26 . Family patterns of coping and decision making may also shape patient involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, physicians and parents may fail to engage children and adolescents in the discussion or actively interfere with their involvement (e.g., interrupting or answering a question that was directed to the child) 24 . The physician’s expectation that the parent will make the final decision is likely to limit attempts to engage the patient in trial or treatment discussions 25, 26 . Family patterns of coping and decision making may also shape patient involvement.…”
Section: Discussionmentioning
confidence: 99%
“…It also consisted of participants who agreed to participate in a study about informed consent. As such, the participants in our sample might have been less distressed or struggled less with the decision than other patients and families who were offered phase I trial participation 25 . Fourth, the sample size was small for analyses that involved parent or patient interview data, and patient interview data were only available for 14- to 21- year-olds.…”
Section: Discussionmentioning
confidence: 99%
“…The research results show that a child's knowledge capabilities, wishes and values are often not taken into account and their participation is prevented. [22][23][24][25][26][27][28][29][30] Healthcare professionals make the decisions on behalf of the children and often on behalf of parents as well. [24,25,27,31] The reasons behind this were the attitudes of the personnel and the parents [26,32,33] and the desire to protect the child.…”
Section: A Child In the Decision-making Related To Treatmentmentioning
confidence: 99%
“…[1][2][3] Prior investigations of adolescent oncology patients have revealed that this population can capably engage in complex decisional processes from the time of diagnosis and treatment 4 through decisions such as fertility preservation, 5 research participation, 6 advanced care planning, 7 and end-of-life decisions. 8 Parents and providers report satisfaction when adolescent oncology patients are able to convey preferences and participate in decision-making discussions.…”
Section: Introductionmentioning
confidence: 99%